Prostate artery embolization for benign prostatic hyperplasia: a retrospective single-center study of clinical outcome - Jon Bjarnason; Johann Pall Ingimarsson; Hjalti Thorisson; Kristbjorn Reynisson; Jon Orn Fridriksson; Baldvin Thorkell Kristjansson; Fernando Bazan (Scandinavian Journal of Urology)
Objective: To evaluate clinical outcome and complications of prostate artery embolization (PAE) in Iceland, using the International Prostate Symptom Score (IPSS), quality of life (QoL) and catheter freedom to measure clinical success.